White Peony (Fermented Camellia sinensis) Polyphenols Help Prevent Alcoholic Liver Injury via Antioxidation - Yalin Zhou; Fang Tan; Chong Li; Wenfeng Li; Wei Liao; Qin Li; Guohui Qin; Weiwei Liu; Xin Zhao (Antioxidants, 2019)
White peony is a type of white tea (Camellia sinensis) rich in polyphenols. In this study, polyphenols were extracted from white peony. In vitro experiments showed that white peony polyphenols (WPPs) possess strong free radical scavenging capabilities toward 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). Long-term alcohol gavage was used to induce alcoholic liver injury in mice, and relevant indices of liver injury were examined. WPPs effectively reduced the liver indices of mice with liver injury. The serum levels of aspartate aminotransferase (ATS), alanine aminotransferase (ALT), alkaline phosphatase (ALP), triglycerides (TG), total cholesterol (TC), blood urea nitrogen (BUN), nitric oxide (NO), and malondialdehyde (MDA) were downregulated, while those of albumin (ALB), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) were upregulated. WPPs also reduced the serum levels of interluekin-6 (IL-6), interluekin-12 (IL-12), tumor necrosis factor-alpha (TNF-α), and interferon-gamma (IFN-γ) in mice with liver injury. Pathology results showed that WPPs reduced alcohol-induced liver cell damage. Quantitative polymerase chain reaction (qPCR) and western blot results revealed that WPPs upregulated the mRNA and protein expressions of neuronal nitric oxide synthase (nNOS), endothelial nitric oxide synthase (eNOS), manganese superoxide dismutase (Mn-SOD), cupro−zinc superoxide dismutase (Cu/Zn-SOD), and CAT and downregulated iNOS expression in the liver of mice with liver injury. WPPs protected against alcoholic liver injury, and this effect was equivalent to that of silymarin. High-performance liquid chromatography revealed that WPPs mainly contained the polyphenols gallic acid, catechinic acid, and hyperoside, which are critical for exerting preventive effects against alcoholic liver injury. Thus, WPPs are high-quality natural products with liver protective effects.